THE USE OF SOCIAL MEDIA IN BANKS TO ENGENDER THE EMPOWERMENT OF WOMEN AND THEIR FINANCIAL INCLUSION IN ARAB COUNTRIES - Yusef Ali Yusef Yakubi; B. Basuki; Rudi Purwono (Bank Indonesia, 2020)
This study aims to classify and interpret the interacted communications between banks and users on social media and understand the role of these digital platforms to enhance woman empowerments and financial inclusion in banks in Arab countries. 100 users of banks’ social media were selected from 5 leading banks in 5 Arab countries and their interactive utterances were classified, analyzed and interpreted. Content analysis tools were applied. The study reveals these key results: First, the use of social media in banks entails two-fold empowerment dimensions that are mutually beneficial for Users and Banks. Second, both flows of utterances either from “User to Banks” or “Banks to Users” demonstrate that the highest ratios of the shared content are more closely associated with financial inclusion dimensions than user’s empowerment aspects. Third, women are found more engaged in social and emotional involvements than men who show a relatively higher interest in banks’ financial services and products. It is also found that Banks use social media to raise social and economic themes that support women in the region. However, the second and third results imply a gender gap in financial inclusion since females still lag behind. This study is different by highlighting the power of banks’ social networks to trigger important gender and economic development themes in a highly conservative society and contribute to literature by analyzing and interpreting the shared content from three extensive outlooks which yield ample details and draw implications for banks’ management and social media policy makers and regulators.